THE RELATIONSHIP BETWEEN WORK EFFICACY WITHJOB INSECURITY ON PRODUCTION EMPLOYEESPT “X” SEMARANG - Rini Sulistyawati; Harlina Nurtjahjanti; Unika Prihatsanti (Faculty of Psychology, Diponegoro University, 2018)
Post ACFTA, ASEAN harmonization program as an effort towards the ASEAN Economic Community (AEC) will be implemented in 2015. Integration will impact on various sectors include traditional herb medicine industry. The inability of the organization to face these conditions can lead to the threat of layoffs and made employees experience job insecurity. Therefore work efficacy to minimize the perceived job insecurity is needed by employees.The purpose of this research is to find out the relationship between work efficacy with job insecurity production employees of PT